STRUCTURAL REFINEMENT OF [Y1-xCax]SrBaCu2.80(PO4)0.20Oy - González González, Juan Carlos (2000)
[Y1-xCax]SrBaCu2.80(PO4)0.20Oy samples with 0.10 ≤ x ≤ 0.40 were syntherized using the solid state reaction technique. X-ray diffraction patterns show that all the compounds crystallized into a 123 tetragonal structure. The analysis of the structure with Rietveld refinement were made using a model that contains one Cu(2) in four coordination and not in five coordination as in the other 123 tetragonal structures. This fact allows that Tc increase with Ca concentration. All samples are superconductors as reported in a previous paper.